Novel SCNN1A gene splicing-site mutation causing autosomal recessive pseudohypoaldosteronism type 1 (PHA1) in two Italian patients belonging to the same small town - Gregorio Serra; Vincenzo Antona; Maria Michela D'Alessandro; Maria Cristina Maggio; Vincenzo Verde; Giovanni Corsello (BMC, 2021)
Abstract Introduction Pseudohypoaldosteronism type 1 (PHA1) is a rare genetic disease due to the peripheral resistance to aldosterone. Its clinical spectrum includes neonatal salt loss syndrome with hyponatremia and hypochloraemia, hyperkalemia, metabolic acidosis and increased plasmatic levels of aldosterone. Two genetically distinct forms of disease, renal and systemic, have been described, showing a wide clinical expressivity. Mutations in the genes encoding for the subunits of the epithelial sodium channels (ENaC) are responsible for generalized PHA1. Patients' presentation We hereby report on two Italian patients with generalized PHA1, coming from the same small town in the center of Sicily. The first patient is a male child, born from the first pregnancy of healthy consanguineous Sicilian parents. A novel SCNN1A (sodium channel epithelial subunit alpha) gene mutation, inherited from both heterozygous parents, was identified by next generation sequencing (NGS) in the homozygous child (and later, also in the heterozygous maternal aunt). A more detailed family history disclosed a possible related twenty-year-old girl, belonging to the same Sicilian small town, with referred neonatal salt loss syndrome associated to hyperkalemia, and subsequent normal growth and neurodevelopment. This second patient had a PHA1 clinical diagnosis when she was about 1 year old. The genetic investigation was, then, extended to her and to her family, revealing the same mutation in the homozygous girl and in the heterozygous parents. Conclusions The neonatologist should consider PHA1 diagnosis in newborns showing hyponatremia, hyperkalemia and metabolic acidosis, after the exclusion of a salting-loss form of adrenogenital syndrome. The increased plasmatic levels of aldosterone and aldosterone/renin ratio, associated to a poor response to steroid administration, confirmed the diagnosis in the first present patient. An accurate family history may be decisive to identify the clinical picture. A multidisciplinary approach and close follow-up evaluations are requested, in view of optimal management, adequate growth and development of patients. Next generation sequencing (NGS) techniques allowed the identification of the SCNN1A gene mutation either in both patients or in other heterozygous family members, enabling also primary prevention of disease. Our report may broaden the knowledge of the genetic and molecular bases of PHA1, improving its clinical characterization and providing useful indications for the treatment of patients. Clinical approach must be personalized, also in relation to long-term survival and potential multiorgan complications.